Identification of Biomarker for Stunting Through Prioritization of Gene-Assosiated Variants - Wibowo, Anisa Devi Kharisma; Puspitaningrum, Anisa Nova; Ma’ruf, Muhammad; Irham, Lalu Muhammad; Supadmi, Woro; Kartikasari, Ayu Lifia Nur; Adikusuma, Wirawan; Chong, Rockie; Firman, Firman; Nugraha, Media Fitri Isma Isma; Siswanto, Lalu Muhammad Harmain; Khairi, Sabiah; Pranata, Satria (Media Farmasi: Jurnal Ilmu Farmasi, 2024)
Stunting is a condition of impaired growth and development in children due to chronic nutritional disorders or infections. The risk factor for stunting is dominated by disease during 1000 days of life. The incidence of stunting in Indonesia is 21.6%, according to the Indonesian Nutrition Status Survey (SSGI) results. This study aimed to identify stunting biomarkers based on the priority scoring of gene variants. Identification of stunting risk genes used the Genome-Wide Association Studies (GWAS) approach and Haploreg v4.1. We found 33 genes that identifies as stunting risk gene. And then, we prioritize based on two functional annotation categories: missense-nonsense and cis-expression quantitative trait loci (cis-eQTL). Our analysis found 4 genes as biological stunting risk genes: MTRR, TTF1, CASP1, and CARD17. This research demonstrates the integration of genomic variants and bioinformatics approaches to reveal biological insights for stunting.